Thromboprophylaxis during the Pregnancy-Puerperal Cycle - Literature Review - Sanches, Suzanna Maria Viana; Cerqueira, Monique Magnavita Borba da Fonseca; Junqueira, Patrícia Lima; Gomez, Miriam Takayanagi (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Objective To identify current strategies and recommendations for venous thromboembolism prophylaxis associated with the pregnancy-puerperal cycle, a condition of high morbidity and mortality among women.Methods The literature search was performed between May and October 2019, using the PubMed database, including papers published in Portuguese, English and Spanish. The terms thromboembolism (Mesh) AND pregnancy (Mesh) OR postpartum (Mesh) were used as descriptors, including randomized controlled trials, meta-analyses, systematic reviews and guidelines published from 2009 to 2019, presenting strategies for prevention of thromboembolism during pregnancy and the postpartum.Results Eight articles met the inclusion criteria. Many studies evaluated were excluded because they did not address prevention strategies. We compiled the recommendations from the American Society of Hematologists, the American College of Obstetricians and Gynecologists, the Royal College of Obstetricians and Gynecologists, the Society of Obstetricians and Gynaecologists of Canada, the American College of Chest Physicians and the Royal Australian and New Zealand College of Obstetricians and Gynaecologists.Conclusion: There are some gaps in the research, and clinical studies with appropriate methodology are needed to support decisions made regarding the risk of thromboembolism in the perigestational period. Thus, the attention of the professionals involved in the care of pregnant and postpartum women is crucial, as it is a condition associated with high morbidity and mortality.
Keywords: thromboembolism; thrombosis; pregnancy; postpartum; disease prevention